2020
DOI: 10.34172/jcs.2020.025
|View full text |Cite
|
Sign up to set email alerts
|

Death Anxiety and Life Expectancy among Older Adults in Iran

Abstract: Introduction: Life expectancy is one of the indices used to analyze health status. This index changes during aging as a result of a variety of incidents, diseases, stress, and anxiety. Death anxiety is one of the problems that can turn into a deadly fear. This study was aimed to determine the association between life expectancy and death anxiety among older adults in Tehran, Iran. Methods: In this correlational descriptive study, 208 older adults aged ≥60 years, who had referred to adult daycare centers in Teh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Death anxiety has been a subject of research among different population groups. In studies among cancer patients and older adults, death anxiety was reported to be moderate to high, and higher death anxiety was associated with lower quality of life 6,7 . Determinants of death anxiety are also varied among different groups since individuals' ideas about death are influenced by a variety of demographic, social, cultural, psychological, and health aspects 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Death anxiety has been a subject of research among different population groups. In studies among cancer patients and older adults, death anxiety was reported to be moderate to high, and higher death anxiety was associated with lower quality of life 6,7 . Determinants of death anxiety are also varied among different groups since individuals' ideas about death are influenced by a variety of demographic, social, cultural, psychological, and health aspects 8 …”
Section: Introductionmentioning
confidence: 99%
“…In studies among cancer patients and older adults, death anxiety was reported to be moderate to high, and higher death anxiety was associated with lower quality of life. 6,7 Determinants of death anxiety are also varied among different groups since individuals' ideas about death are influenced by a variety of demographic, social, cultural, psychological, and health aspects. 8 With the emergence of the coronavirus disease 2019 (COVID- 19) pandemic, encountering death either in relatives or acquaintances, misleading information, and uncertain reports about the disease lead to numerous psychological consequences, such as fear and death anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…A Canadian study reported that men and women who had depression live a substantially higher proportion of their life in an unhealthy state compared to their counterparts without depression [ 20 ]. Another research showed that the negative correlation between anxiety and life expectancy required using appropriate methods to improve life expectancy [ 21 ]. Loss of life expectancy in most people with mental disorders such as depression or anxiety is accounted for by a broad range of causes of death [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fear of death scored lowest in this study is different from that in Iran. Death anxiety among older Iranians was relatively high [ 42 ]. Nearly 80% of the community-dwelling older adults in this study suffer from chronic diseases but 98.05% have no care problems according to their self-assessments.…”
Section: Discussionmentioning
confidence: 99%